Gait Planning and Stability Analysis of Lower Limb Wearable Walkers - Wang Xin; Yan Peifeng (Jixie chuandong)
The hemiplegic patients can't walk on their own due to the movement obstacle of one side of the lower limb caused by brain injury. The lower limb wearable walker can help them get the ability to walk, but if they want to walk out the normal gait like ordinary people, the gait planning of the lower limb wearable walker is necessary. Gait planning is the basis and key for man-machine coupling walking and maintaining stability. Firstly, through the analysis of the movement of each joint of the lower limb, the overall mechanism of the lower limb wearable walker is designed. Secondly the gait planning is carried out. The part between the joints of the leg of the walker is regarded as a homogeneous rigid link, nine special time points of each joint in the complete walking cycle are extracted, and the coordinates and angles of the joints at each time point are analyzed. Combined with the cubic spline interpolation method in Matlab software, the motion track of the joints is simulated. Finally,the gait planning data is analyzed to obtain the coordinates of the barycenter projection point, fit the motion track of the barycenter projection point, and analyze whether the track always falls in the support area. The results prove that the barycenter projection point is always in the supporting area, which indicates that the gait planning meets the stability requirements.